Effetti del trattamento con un analogo dell'ormone giovanile sulla fertilità di Tenebrio molitor L. (Coleoptera Tenebrionidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Adult pairs of Tenebria malitar were orally given methoprene during the 28 days following their metamorphosis, and the eggs laid during this period were collected.On average, the treated pairs laid fewer eggs than the controls.The eggs were divided into three classes: dry white, non fertilized eggs; dry black eggs in which the embryos died when at different stages of its development; hatched eggs (which the larva left).All three classes of eggs varied according to the given dose: the higher was the dose, the higher was the number of dry white eggs and of dry black eggs, whereas the number of hatched eggs decreased.The length of the treatment too influenced the per cent proportion between all three the classes: during the second half of the treatment the number of white dry eggs and of the hatched eggs increased, whereas the dry black eggs decreased.Some hypothesis were made, with the purpose to explain these facts.